Jussieu, ou les infortunes de la modernité - Laurent Alberti (In Situ)
The site of Jussieu University in Paris is emblematic of the issues associated with architectural heritage from the second half of the 20th century, because of the stakeholders involved as much as the built works.The creation, and then the realization in two stages of the Faculty of Sciences in Paris, illustrate how the ambitions of a Gaullian planning republic were materialized through the "Cassan bars" and especially the "grill" of Édouard Albert, symbol of the monumental and institutional modernity proper to the Trente Glorieuses.At the end of this period, a debate began concerning the legitimacy of this “project-object dynamic”. The evolution of university practices and the rejection of functionalism and orthodox modernism left the “grill” unfinished. After the cultural crisis of 1968, the public health crisis brought on by the presence of asbestos triggered a major renovation of the facility starting in 1998.People in charge of this renovation, who claimed a deep respect for the architecture of the building, actually modified the grill heavily. This illustrates the current confusion, where evocation and image takes over the deontology of conservation, casting aside the authenticity of the work. At the same time, the construction of the Institute du Monde Arabe (IMA) transforms the relationship between the city and this building, born under the influence of the charter of Athens. The IMA, as a sophisticated postmodern vector, reformulates the link between the unfinished Jussieu and the traditional Parisian fabric by connecting it to its city blocks.This evolution makes Jussieu a rare example of stratified significant 20th century architectural heritage. This significance corrupts the idealized figure of the grill in a paradoxical positioning that saves the buildings from demolition, but seemingly promotes the dissolution of the work.